Health Education in Primary Schools: A Difficult Task - Masson, Philippe; Racodon, Michael; Porrovecchio, Alessandro; Duchateau, Guillaume (Central European Journal of Educational Research, 2022)
This study was conducted in a medium-sized French city, in a neighbourhood falling into poverty, with children aged from 9 to 10 years old. Its aim is to build an adapted strategy to improve children’s healthy habits. Our study was based on a mixed methods interdisciplinary approach using interviews, questionnaires, sleep diaries and accelerometers. The unemployment rate of the target population is above 40%, and the families have four children on average. The children of the sample (N=29) practice less physical activity than recommended by the institutions in charge of health matters. The parents correctly manage the sleep cycles of their children, and stand firm when they have to go to school the next day. When the next day is a non-school day, children play more video games in the evening, both on their own and with their families. Healthy habits can be improved through cooperation with the various members of the educational community (parents, teachers and structures in charge of the children). Since it is difficult to manage health education solely during PE classes, this process must be continued both inside and outside school by the community, even more so the family.